1987
DOI: 10.1111/j.1365-2125.1987.tb03034.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of azathioprine to 6‐thioguanine nucleotides in patients with pemphigus vulgaris.

Abstract: Azathioprine metabolism, to red cell 6‐thioguanine nucleotides (6TGN), was studied in four patients with pemphigus vulgaris. Throughout treatment blood samples were taken for red cell 6TGN assay and differential white cell counts. Metabolite steady‐state occurred in three patients in 2, 2 and 4 months respectively. In the fourth patient red cell 6TGN concentrations increased slowly over 3 years. There was a significant negative correlation between 6TGN concentrations and the white blood cell count (rs = −0.92,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…According to the literature, the estimated half-life of 6-TGN in EC is 3-13 days, with an average of about 5 days [17,19,27]. However, much longer half-lives have been reported [28], and our observation in one patient may be explained by 6-TGN accumulation caused by prolonged elimination.…”
Section: Discussionmentioning
confidence: 54%
“…According to the literature, the estimated half-life of 6-TGN in EC is 3-13 days, with an average of about 5 days [17,19,27]. However, much longer half-lives have been reported [28], and our observation in one patient may be explained by 6-TGN accumulation caused by prolonged elimination.…”
Section: Discussionmentioning
confidence: 54%
“…Hanai et al reported that leukocytopenia was observed when 6TGN levels exceeded 320 pmol/8 × 10 8 RBC, with an incidence of approximately 20% 6. And Lennard et al showed that the patient had leukocytopenia when 6TGN level went over 300 pmol/8 × 10 8 RBC 10. Thus, less than 300 pmol/8 × 10 8 RBC would not be high.…”
Section: Discussionmentioning
confidence: 99%
“…6 ninphosphoribosyltransferase (HRPT) in seine aktiven Metaboliten, die 6-Thioguaninnukleotide (6-TGN). Hierbei ist von Bedeutung, daß es Wochen bis Monate (manchmal bis drei Jahre) dauern kann, bis ein "Steady State" der Konzentration der 6-TGN erreicht wird [29,30]. Dies mag eine Erklärung für den verzögerten Wirkungseintritt von Azathioprin darstellen, so daß der klinische Effekt teilweise erst nach vier bis sieben Monaten zu beobachten ist.…”
Section: Klinische Pharmakologieunclassified